EFFICACY OF RASMANIKYA ALONG WITH GUDUCHYADI CHURNA IN MANAGEMENT OF PSORIASIS - Damle Neena D. (International Journal of Applied Ayurved Research, 2015)
Psoriasis affects 1% to 3% of the world's population. Most patients have limited psoriasis involving <5% of their body surface. There is a strong association between psoriasis and HLA B13, B17, and B27,which shows genetic connection of psoriasis. Peak age of onset is bimodal (adolescents and at 60 yr of age). Men and women are equally affected.The main objective of the study was to assess the role of Rasmanikya along with Guduchyadi churna in Psoriasis. Study was conducted at Dr. D. Y. Patil College of Ayurved & Research Institute, Nerul, Navi-Mumbai.Total 10 patients were enrolled in this trial. Both male and female patients between the age group of 18 and 60 years were selected for this study. Rasamanikya 50mg+ Guduchyadi churna 3gms was given twice daily before food with warm water. The effect of therapy was assessed based on improvement obtained in signs and symptoms of the patients. The patients showed up to 60 percent improvement gradually after 2months of treatment.